The Role Of Islamic Capital Markets In Promoting Sustainable Investment - Loso Judijanto; Wahyudin Rahman; Jaka darmawan; Sagira Sagira (Journal of Islamic Economy, 2025)
The Islamic capital market plays a strategic role in promoting sustainable investment by upholding Sharia principles based on ethics, justice, and sustainability. Sustainable investment in this context not only seeks financial returns but also considers the social and environmental impacts of investment decisions. As an alternative financing option aligned with Islamic principles, the Islamic capital market prohibits practices such as usury (riba), excessive uncertainty (gharar), and investments in sectors that contradict Islamic moral values. Financial instruments such as green sukuk offer solutions to support environmentally friendly and socially responsible projects. Additionally, the Islamic capital market encourages investment in companies that comply with Sharia principles and demonstrate a strong commitment to sustainability. This study aims to examine the contribution of the Islamic capital market in fostering more sustainable investments. By analyzing financial instruments and policies implemented in this sector, the study is expected to provide insights into the potential of the Islamic capital market as a tool for achieving investment goals that prioritize sustainability and align with the principles of Islamic economics.